Ocimum sanctum powder as a Dusting material in Latent fingerprints - An Observational study in Forensic - Hariprasath T.K, Dr. Abirami Arthanari, Dr.S.Rajeshkumar (Drugs and Cell Therapies in Hematology, 2021)
Introduction: Ocimum sanctum belongs to the family Lamiaceae. It is commonly known as “Tulsi” and has been used for thousands of years in Indian System of Medicine for its diverse healing properties. Extracts of this plant, particularly of leaves, have been traditionally used for various ailments in the traditional Ayurvedic and Unani system and moisture components of the latent print. The powder is taken in a clean dry Petri dish and dusted on the surfaces wherever the fingerprints were present. Aim: The aim of the research is to find a new technique for visualising the latent fingerprints. Results: Therefore using the tulsi leaves powder (Ocimum sanctum), the fingerprints were obtained similar to that of commercially used powder. So we can get visible fingerprints and also we can make fingerprints using the powder. Conclusion: Findings revealed that the nanoparticle powders and reagent performed on par with the existing commercial powders and exhibited higher selectivity. Nanoparticle synthesis from low-cost precursors in this research did not require special equipment, addition of resins or adhesives, or surface passivation.